CRISPR-Cas9 as a tool for gene therapy in Machado-Joseph disease: silencing ATXN3 and CAG expansion correction - Conceição, André Filipe Vieira da (2019)
Dissertação de Mestrado em Biologia Celular e Molecular apresentada à Faculdade de Ciências e Tecnologia